ADOPSI TANPA PENGADILAN DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Rahmadani, Gema; Pagar, Pagar (Pusat Studi Gender dan Anak, 2024)
Child adoption in Indonesia is governed by two main legal systems, namely positive law and Islamic law, which have different legal principles and consequences. In positive law, child adoption must go through the courts as stipulated in Article 1 Paragraph 9 of the Child Protection Law No. 23 of 2002, to provide legal protection and certainty of rights for both adopted children and adoptive parents. Meanwhile, Islamic law does not recognise a nasab relationship between the adopted child and the adoptive parents. Adopted children do not have inheritance rights from adoptive parents and remain connected to their biological lineage. The practice of adoption without a court order has various adverse legal implications. In the perspective of positive law, the absence of legal ratification can eliminate the rights and obligations between the adopted child and the adoptive parents, as stated in Article 45 Paragraph (1) and Article 46 Paragraphs (1 and 2) of Law Number 1 Year 1974. This also has the potential to trigger legal disputes that cannot be resolved formally. This research uses a qualitative method based on literature review with a focus on analysing the regulation and concept of adoption according to both legal perspectives. The results show that adopting a child without going through a court process not only violates positive legal rules but also has the potential to ignore the principles of Islamic law related to child welfare and justice. Therefore, it is important for the community to understand the applicable legal rules so that adoption can be carried out correctly and in accordance with applicable legal provisions.